Neurological outcome of high-risk neonates at 40 weeks of gestational age and at three months of corrected gestational age - Khan, Ameer; Galwa, Anil (International Journal of Contemporary Pediatrics, 2019)
Background: Infants born <30 weeks’ gestation is at increased risk of long-term neurodevelopmental problems compared with term born peers. The predictive value of neuro behavioral examinations at term equivalent age in very preterm infants has been reported for subsequent impairment. Therefore, this study aims to attempt to study incidence of neurological abnormality in high risk neonates in our neonatal intensive care unit. Methods: A prospective cohort observational study was conducted at centre for comprehensive child health, division of neonatology, Pushpanjali Crosslay hospital (Max super speciality hospital, Vaishali), Vaishali, Ghaziabad, Uttar Pradesh, India. Duration of study was October 2014 to September 2015. Seventy-five high risk neonates fulfilling the inclusion criteria admitted at NICU were recruited after taking informed consent from mothers /fathers. Results: Total 75 high risk newborns were studied. Their clinical data was noted, neurodevelopmental, neurosensory examination done at 40 weeks of completed gestational age and also at 3 months on follow up. The data was collected according to pre-decided proforma. Neuro developmental assessment was done by updated Amiel-Tison manual of neurological examination. On follow up at 3 months all the newborns who were normal (54) at 40 weeks were found to be normal (100%) and also all those who were definite abnormal (4) at 40 weeks were found to be definite abnormal (100%). But out of the 17 who were moderately abnormal at 40 weeks, 13 (76.5%) have become normal and 4 (23,5%) remained moderately abnormal and none progressed to definite abnormality. Conclusions: There is lack of awareness regarding dog bite and its management among the rural population.